Does Formal Training in Medical Education and Professional Development Lead to Better Career Outcomes for Clinician Educators?. Issue 5 (May 2020) - Kohli, Amar; Benson, Maggie; Mieczkowski, Alexandra; Spagnoletti, Carla; Rubio, Doris; McNeil, Melissa; Granieri, Rosanne
Abstract : Objectives: Medical school and residency training programs rely on skilled clinician-educators to provide high-quality educational experiences. In 2002, the University of Pittsburgh's Institute for Clinical Research Education created a master's-level degree-granting program in medical education, which now has more than a decade of graduates. Methods: All graduates between 2004 and 2014 were invited to complete an anonymous electronic survey regarding their experiences with the program and their perception of whether the master's program adequately prepared them in domains pertinent to medical educators. Participants also were asked to upload their current curricula vitae (CV) to assess objective measures of academic productivity among program graduates. Results: More than 75% of surveys were completed (47/60) and 75% of CVs were submitted (45/60). Demographics of respondents showed that 66% were woman. The racial demographics of respondents revealed 13% Hispanic/Latino, 28% Asian, and 59% white, respectively. More than 90% of respondents agreed that because they completed the program, they were competent in multiple teaching and learning domains; 94% of respondents believed that they were more effective educators than peers who did not complete this degree. CV abstraction revealed that 98% of respondents currently held academic positions. Number of publications and number of years since program graduation were used to determine the rate of productivity of the graduates. Twenty-six graduates (58%) successfully published at least one peer-reviewed article per year since they graduated. This equated to approximately 3.77 publications per year for these 26 respondents and 2.27 publications per year for the entire cohort. Conclusions: Program graduates attributed their competence in several key domains that are crucial to excellence as a clinician-educator to their participation in the degree-granting program. The results of this study suggest that receipt of a graduate-level degree in medical education develops and enhances teaching skills and academic productivity among clinician-educators. Abstract : This article is a survey of graduates of a master's-level degree-granting program in medical education. The survey encompasses 10 years of graduates and assesses their experiences with the program. In addition, it objectively quantifies their academic productivity through an assessment of their curricula vitae.Supplemental digital content is available in the text.